Synergistic effect of essential oil of thyme extract (EOT) with chemotherapy in esophageal cancer cells: Efficacy of Thyme Oil Extract on Esophageal Cancer Cells - Sattar, Budoor; Jadou, Ayat Subhi; Fadhil, Ola H; Abbas A. Mohammed; Amer T. Tawfeeq (Iraqi Journal of Cancer and Medical Genetics, 2024)
Background: Esophageal cancer is one of the most common causes of cancer-related death in various countries around the world, and thus represents a major global health challenge. This cancer is most often found in the upper and middle parts of the esophagus but can occur anywhere along the length of the esophagus. Aim of study: Essential oils have activity that targets cancer cells and their ability to increase the effectiveness of commonly used chemotherapy, including cisplatin, as they act as antioxidants when given to a cancer patient. Methods: In this study, the volatile oil of Thymus was extracted from the dry leaves of the plant and EOT was detected by the gas chromatography mass spectrometry (GS-MS) method. Cytotoxicity was evaluated by two experiments, one to determine the effect of volatile oil on the esophageal cancer cell line (SKG-4) and to compare chemotherapy when combined with the extract.Results: Essential oil cytotoxicity in 48 hours showed a significant percentage (P < 0.05) at all diluted volumes used, while the highest toxicity (89.016%) was in the diluted volume of 2.5 μl/ml. The same results were also observed for the combination of EOT, and chemotherapy cisplatin used during the trial. A significant percentage (P < 0.05) within 72 hours was observed to show the highest cytotoxicity (70.191%) in the diluted volume of 10 μl/ml, and no difference appeared in cytotoxicity. Conclusions Through this experiment, we concluded that the extract has a toxic effect on the cancer cell line and does not affect the effectiveness of chemotherapy and that the aim of this study is to mitigate the negative effects of chemotherapy.